BETA CHI-SQUARE DISTRIBUTIONS PROPERTIES AND APPLICATIONS - SACRAMENTO, Katia Pires Nascimento do; SACRAMENTO, Vinicius Pereira do (Brazilian Journal of Biometrics, 2022)
In this paper we introduce the distribution of three parameters, called Beta Chi-square distribution (BCHI), is presented and contains the Chi-square distribution as a sub-model. Its density function can be expressed as a linear combination of Chi-square density function. Some structural properties of this distribution, how moments, and hazard function are presented. Estimates of the model parameters are performed using the Maximum Likelihood method. We obtain the observed information matrix and discuss inference methods. In order to demonstrate the utility of the distribution, a real data set is analyzed.